Mengedukasi Life Skill Kearifan Lokal dalam Kemandirian Pangan Masyarakat dalam Pengelolaan Rumah Bibit Sayuran Organik Berbasis Kemitraan PROKLIM (Program Kampung Iklim) Di Kelurahan Sidomulyo Timur – Kota Pekanbaru- Provinsi Riau - Yustina, Yustina; Zulfarina, Zulfarina; Taufik, Hendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This activity aims to improve the Life Skills of Local Wisdom in Independent Management of organic vegetable seed houses and increase the participation of participants towards self-sufficiency in food. This P2M method is the Integrated Real Work Lecture Activity (KUKERTA) of the University of Riau for the period I and III of 2022. This activity was carried out in Sidomulyo Timur Village, Marpoyan Damai District in March - October 2022. The target community is the cadre of the Women Farmers Group (KWT) . Monitoring the activities of implementing the participants' life skills includes: 1) Proposing problems and solutions, 2). Implementation activities, 3) Demonstration of activities, 4) Application of activity results, 5) Integration of crop yields and benefits and constraints. The results of monitoring activities show the success of these five activity indicators which are supported by the existence of local wisdom such as the culture of mutual cooperation, so that life skills in managing seed houses can increase and the participation of the Beringin Indah community in the village of Sidomulo Timur in maximizing the use of the yard by planting vegetables using fertilizers. organic, but the new harvest is sufficient for the local community in RW 06 covering only 12 RT. In conclusion, this community service activity is very appropriate, appropriate/relevant, systematic, coherent and fakual to improve people's life skills.